Influence of Institutional Inclusive Policy on Curriculum Adaptation and Participation of Students With Disabilities on Academic Activities in Public Universities in Kenya - Karanja, David Njuguna; Musyoka-Kamere, Isabella; Wawire, Violet (Journal of Education and Training, 2022)
Globally, it is estimated that close to 140 million learners are out of school and among them are those with disabilities as a result of physical, mental and sensory impairments. Out of that number, it is further estimated that 70% of learners with disabilities can attend and benefit from regular education programs as long as effective institutional changes that are guided by sound inclusive policies are done. So, this study examined institutional inclusive policies on curriculum adaptation, and how the policies affect the way Students with Disabilities participate academically. The study was guided by the social model theory of disability. A descriptive research design and a comparative approach were used to scientifically compare curriculum adaptation in Kenyatta and Jomo Kenyatta University of Agriculture and Technology Universities which were purposively chosen as the sample owing to their longer establishment. Lecturers teaching and Students with Disabilities enrolled in different programs were targeted. The two registrar academics in charge of admission and the two coordinators of the disability offices from both universities were purposively selected. Data collection instruments were interviews, questionnaires, observation guide, focus group discussions and document analysis. The findings showed that the appropriate adaptation of the University curriculum has not been fully made to respond to the diverse academic needs of all learners with various disabilities.